2021
DOI: 10.2147/copd.s321197
|View full text |Cite
|
Sign up to set email alerts
|

High 24-Hour Respiratory Symptoms and Low Physical Activity in the Stable COPD Romanian Cohort of SPACE Study

Abstract: This study assessed the characteristics and the relationship between symptoms in any part of the 24-hour (24-h) day, physical activity level (PAL), and other clinical and functional outcomes in stable COPD patients. Patients and Methods: Out of the 2162 patients enrolled in the SPACE study (The Symptoms and Physical Activity in COPD patients in Europe, clinicaltrials.gov NCT03031769), 406 (18.8%) were recruited from Romania. Here, we present the Romanian cohort results. Eligible patients were adults with age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Values are presented as OR (95% CI). Sedentary behavior and decreased physical activity due to exertional dyspnea are one of the main life characteristics of patients with COPD, and this lifestyle is associated with poor outcomes in patients with COPD 34 : physical activity level and health status of patients with COPD, 35 the symptom burden, [36][37][38] prolonged sedentary time, and decreased physical activity levels can all affect the mortality rate and the number of exacerbations 39 in patients with COPD. A study with a mean follow-up of 2.7 years found that the number of daily steps in patients with COPD decreased periodically over time, and this change was significantly correlated with the degree of airflow limitation in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Values are presented as OR (95% CI). Sedentary behavior and decreased physical activity due to exertional dyspnea are one of the main life characteristics of patients with COPD, and this lifestyle is associated with poor outcomes in patients with COPD 34 : physical activity level and health status of patients with COPD, 35 the symptom burden, [36][37][38] prolonged sedentary time, and decreased physical activity levels can all affect the mortality rate and the number of exacerbations 39 in patients with COPD. A study with a mean follow-up of 2.7 years found that the number of daily steps in patients with COPD decreased periodically over time, and this change was significantly correlated with the degree of airflow limitation in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…It would be even more beneficial to each patient if this program could be multidisciplinary or cross-domain, covering multiple specialties and extending far beyond hospital care to community rehabilitation services as well, with the inclusion of tertiary, secondary, and/or primary-care facilities/levels. Some experts recommend, according to COVID-19’s clinical signs and symptoms, that the patient’s rehabilitation has to include pulmonary, physical, and psychosocial rehabilitation, as in chronic obstructive pulmonary disease (COPD) [ 17 , 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with stable COPD, still feel fatigued, dizzy and often shortness of breath despite all medical treatments. [ 4 ] In addition, all the treatments mentioned above may lead to certain side effects of drugs, such as heart toxicity, risks of pneumonia, or gastrointestinal adverse reactions. [ 5 ] The pathophysiological basis of fatigue in COPD is complex, and its precise mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%